PEMANFAATAN E-COMMERCE DALAM PENGEMBANGAN BISNIS MENURUT PERSPEKTIF EKONOMI ISLAM DI ERA COVID 19 - Mutiara Puspa Garini; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
Since the Covid 19 virus has changed the declining economy in the world, the use of internet technology is very much needed, especially in the business world for business development which must continue during this pandemic, due to government policies such as PSBB (Large-scale social restrictions). Internet technology that can be used is such as e-commerce. But in utilizing e-commerce in business development, you must continue to use an Islamic economic perspective in your business. The purpose of this study is a follow-up study from (Nurlaela 2018) entitled The Effectiveness of Using E-commerce Media on Increasing Depok MSME Revenues Seen from Business Ethics. Which gives advice to further researchers to see how much benefit is obtained if the company can implement e-commerce in its business interests. The method used in this research is descriptive and the type of data used is library research. The results in this study are that in Islamic economics it is allowed to use e-commerce in business development during this covid 19 period, but still with the rules that have been set according to the perspective of Islamic economics, namely by remembering the principles of buying and selling Islam